Effect of atherosclerosis on 5-year risk of major vascular events in patients with transient ischaemic attack or minor ischaemic stroke: an international prospective cohort study. Issue 4 (April 2023) - Lavallée, Philippa C; Charles, Hugo; Albers, Gregory W; Caplan, Louis R; Donnan, Geoffrey A; Ferro, José M; Hennerici, Michael G; Labreuche, Julien; Molina, Carlos; Rothwell, Peter M; Steg, Philippe Gabriel; Touboul, Pierre-Jean; et al.
Summary: Background: The prevalence of atherosclerosis and the long-term risk of major vascular events in people who have had a transient ischaemic attack or minor ischaemic stroke, regardless of the causal relationship between the index event and atherosclerosis, are not well known. In this analysis, we applied the ASCOD (atherosclerosis, small vessel disease, cardiac pathology, other causes, and dissection) grading system to estimate the 5-year risk of major vascular events according to whether there was a causal relationship between atherosclerosis and the index event (ASCOD grade A1 and A2), no causal relationship (A3), and with or without a causal relationship (A1, A2, and A3). We also aimed to estimate the prevalence of different grades of atherosclerosis and identify associated risk factors. Methods: We analysed patient data from TIAregistry.org, which is an international, prospective, observational registry of patients with a recent (within the previous 7 days) transient ischaemic attack or minor ischaemic stroke (modified Rankin Scale score of 0–1) from 61 specialised centres in 21 countries in Europe, Asia, the Middle East, and Latin America. Using data from case report forms, we applied the ASCOD grading system to categorise the degree of atherosclerosis in our population (A0: no atherosclerosis; A1 or A2: atherosclerosis with stenosis ipsilateral to the cerebral ischaemic area; A3: atherosclerosis in vascular beds not related to the ischaemic area or ipsilateral plaques without stenosis; and A9: atherosclerosis not assessed). The primary outcome was a composite of non-fatal stroke, non-fatal acute coronary syndrome, or cardiovascular death within 5 years. Findings: Between June 1, 2009, and Dec 29, 2011, 4789 patients were enrolled to TIAregistry.org, of whom 3847 people from 42 centres participated in the 5-year follow-up; 3383 (87·9%) patients had a 5-year follow-up visit (median 92·3% [IQR 83·4–97·8] per centre). 1406 (36·5%) of 3847 patients had no atherosclerosis (ASCOD grade A0), 998 (25·9%) had causal atherosclerosis (grade A1 or A2), and 1108 (28·8%) had atherosclerosis that was unlikely to be causal (grade A3); in 335 (8·7%) patients, atherosclerosis was not assessed (grade A9). The 5-year event rate of the primary composite outcome was 7·7% (95% CI 6·3–9·2; 101 events) in patients categorised with grade A0 atherosclerosis, 19·8% (17·4–22·4; 189 events) in those with grade A1 or A2, and 13·8% (11·8–16·0; 144 events) in patients with grade A3. Compared with patients with grade A0 atherosclerosis, patients categorised as grade A1 or A2 had an increased risk of the primary composite outcome (hazard ratio 2·77, 95% CI 2·18–3·53; p<0·0001), as did patients with grade A3 (1·87, 1·45–2·42; p<0·0001). Except for age, male sex, and multiple infarctions on neuroimaging, most of the risk factors that were identified as being associated with grade A1 or A2 atherosclerosis were modifiable risk factors (ie, hypertension, dyslipidaemia, overweight, smoking cigarettes, and low physical activity; all p values <0·025). Interpretation: In patients with transient ischaemic attack or minor ischaemic stroke, those with atherosclerosis have a much higher risk of major vascular events within 5 years than do those without atherosclerosis. Preventive strategies addressing complications of atherosclerosis should focus on individuals with atherosclerosis rather than grouping together all people who have had a transient ischaemic attack or minor ischaemic stroke (including those without atherosclerosis). Funding: AstraZeneca, Sanofi, Bristol Myers Squibb, SOS Attaque Cérébrale Association.